Pediatric vs. adult NAFLD to MAFLD transition: a welcome but tangled path - Angelo Colucci; Maria Chiara Rocco; Anna Giulia Elena De Anseris; Lucia Nazzaro; Pietro Vajro; Claudia Mandato (Open Exploration Publishing Inc., 2021)
The term non-alcoholic fatty liver disease (NAFLD) appears unfitting both in adults and in children. As obesity and metabolic syndrome play a relevant pathogenic role, an international group of adults' liver disease experts has proposed to rename this condition metabolic (dysfunction)-associated fatty liver disease (MAFLD). While this new more appropriate and useful definition has mostly been met with good reactions in adults, it may present a tangled path in pediatrics. Here we further stress the recommendations of the North American and the European Societies for Pediatric Gastroenterology, Hepatology and Nutrition that a hyperechogenic liver in a child affected by obesity or overweight with chronically elevated liver enzymes should not be assumed to have NAFLD only. Especially in those patients who are not in the classic age range or who have particularly severe laboratory anomalies, other genetic, metabolic (inborn errors of metabolism, IEM), endocrine, intestinal and hepatic pediatric-onset conditions, should in fact be excluded, particularly when response to a weight loss trial is not available. The term pediatric fatty liver disease (PeFLD) with three subtypes [1. contextual diagnosis of an IEM; 2. metabolic (dysfunction)-associated fatty liver; 3. unknown cause of fatty liver] has recently been proposed aiming to separate true MAFLD from IEM and/or the other above mentioned conditions, which may be rare when considered individually but represent a large group when considered collectively. Although the cost-effectiveness ratio of this attitude is still indeterminate, it is likely that the advantage of the early identification of a specifically treatable pediatric-onset liver disease associated to/mimicking MAFLD would be rewarding.